Influence of disturbed conditions of reparative regeneration of bone tissue on the dynamics of thyroid hormones - Q. .. Guangda (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Managing bone tissue regeneration is a key problem in traumatology and orthopedics. The researches proved that thyroid hormones affect hemostasis and reparative regeneration of bone tissue favorably and promote osteogenesis and bone consolidation. The aim of this research is to study the influence of disturbed reparative regeneration on the concentration of thyroid hormones in blood in the dynamics. Experimental research on rabbits (n = 12) with modelling of disturbed reparative regeneration revealed disorder in thyroid hormones synthesis and different directions of T3 and unbound T3 production on the 35th day when the maximum decrease of T3 (2 times) and unbound T3 (1.5 times) compared to normal values was registered. The analysis of production of T4 and unbound T4 revealed suppression of the values from the 1st to 50th day and gradual increase in unbound T4 from the 50th day. The most significant manifestation of thyroid gland reaction on the disturbed reparative regeneration of shin bones was the decrease in T3 and peripheral conversion of thyroid hormones up to 50th day with formation of false joint in these terms.